Fenomena Bilingualisme Arab-Indonesia dalam Dialog Film Negeri 5 Menara - Ulpah, Siti Marya; Tatang, Tatang (Qismul Arab: Journal of Arabic Education, 2024)
This study was conducted due to the issue of bilingualism that arises in the film Negeri 5 Menara in the form of code-switching and code-mixing. In the context of cinema, bilingualism serves as a social reflection, a narrative tool, and even a cultural strategy. This is important for understanding how language can reinforce and preserve cultural values in popular media. This research aims to analyze the phenomenon of bilingualism in the form of Arabic code switching and code mixing within Indonesian language speech in the film Negeri 5 Menara. This film was chosen because it explicitly portrays life in an Islamic boarding school. The research employs a descriptive qualitative method. The data consists of transcriptions of Indonesian speech that include Arabic code switching and code mixing. The data source for this research is the film Negeri 5 Menara, directed by Affandi Abdul Rachman. Data collection techniques include listening and transcription. The data were analyzed using data reduction, data presentation, data verification, and conclusion. The conclusion of this study reveals the phenomenon of bilingualism in this film, manifested in the form of external code switching and code mixing, as also observed in the novel. External code-switching from Indonesian to Arabic yielded 8 instances, consisting of words, phrases, and clauses, while outer code mixing within Indonesian speech resulted in 23 instances, comprising 14 words, four phrases, 3 clauses, and one blended form. The function of this code-switching and code-mixing is to demonstrate the characters' proficiency in using Arabic.